Mechanistic Insights into the Electrochemical Reduction of CO2 on Cyclo[18]carbon using Density Functional Theory Calculations. Issue 8 (25th March 2020) - Qin, Binhao; Zhang, Qiao; Li, Yuhang; Yang, Guangxing; Yu, Hao; Peng, Feng
Abstract: Cyclo[18]carbon (C18 ) as a special molecular allotrope of carbon composed of two‐coordinate carbon atoms has recently been manufactured and characterized by atomic manipulation. Herein, we analyze the electrochemical reduction characteristics of carbon dioxide (CO2 ) on typical carbon materials (graphene, C60, carbon nanotubes and C18 ) using density functional calculations. Encouragingly, C18 shows excellent CO2 reduction activity compared to other carbon materials. Abstract : Material witness : Cyclo[18]carbon, composed of two‐coordinate carbon atoms, has injected fresh blood into the field of carbon materials. It can effectively reduce the energy barrier in the CO2 reduction process and effectively inhibit the formation of H2 .